2022
DOI: 10.1128/spectrum.02149-21
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Hepatitis B Virus RNA Quantification in Untreated and Treated Chronic Patients: a Promising Marker of Infection Follow-Up

Abstract: This study focused on the quantification of circulating HBV RNA by using a standardized and sensitive assay. Thanks to this system we observed a higher difference between circulating HBV DNA and RNA than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This may be solved using a true HBV-RNA international standard (still lacking), which would enable reliable, reproducible HBV-RNA quantification. Recently, we compared HBV-DNA and HBV-RNA levels in 63 treatment-naïve patients with CHB (mostly HBeAg-negative) using a different approach [3] : HBV-DNA was quantified using the WHO international standard (IU/ml), and HBV-RNA using an armored HBV-RNA standard (copies/ml). To compare both magnitudes, HBV-DNA IU were converted into copies using the equivalent IU:copies.…”
Section: Letter To the Editor: Standardization Of Hbv-rna Assay For T...mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be solved using a true HBV-RNA international standard (still lacking), which would enable reliable, reproducible HBV-RNA quantification. Recently, we compared HBV-DNA and HBV-RNA levels in 63 treatment-naïve patients with CHB (mostly HBeAg-negative) using a different approach [3] : HBV-DNA was quantified using the WHO international standard (IU/ml), and HBV-RNA using an armored HBV-RNA standard (copies/ml). To compare both magnitudes, HBV-DNA IU were converted into copies using the equivalent IU:copies.…”
Section: Letter To the Editor: Standardization Of Hbv-rna Assay For T...mentioning
confidence: 99%
“…Buti is on the speakers' bureau for Gilead and AbbVie. David Tabernero 1 Maria Francesca Cortese 1,2 Ariadna Rando-Segura 3,4 Maria Buti 1,5 Francisco Rodríguez-Frías Note: Differences were calculated by subtracting median HBV RNA (log 10 U/ml) from median HBV DNA (log 10 IU/ml), shown by Mak et al [1] in Table 1 for treatment-naïve patients and Table 3 for the baseline sample of nucleos(t)ide-treated patients.…”
Section: O N F L I C T O F I N T E R E S Tmentioning
confidence: 99%
“…Considerable declines of serum HBV RNA were observed under long-term NAs treatment in the vast majority of current studies, and HBV RNA showed a much slower decline than serum HBV DNA, 8,57,59,65,69-83 which could be observed as early as 1 week after treatment. 8 gradually exceeded HBV DNA concentration during treatment, 69,71,72 and HBV RNA could remain detectable despite HBV DNA becoming undetectable in patients under persistent NAs therapy, 65,69,[76][77][78]80,[84][85][86] even in some patients achieving HBsAg clearance. 76,87,88 Contrary to the mainstream findings, it was observed that serum HBV RNA level showed a rise within 4 weeks after NA therapy and began to decline afterward.…”
Section: Dynami C Chang E S Of S Erum Hbv Rna Le Vel S Under Na S The...mentioning
confidence: 99%
“…Recently, Roche has developed an automated assay on the cobas 6800/8800 platforms for the determination of HBV RNA levels in serum or plasma. 19 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%